Kajian Perkumpulan Petani Pemakai Air (P3A) Pasca Reformasi di Provinsi Jawa Tengah - Supadi, Supadi (Department of Civil Engineering, Diponegoro University, 2008)
Irrigation Area in Central Java Provincy is managed by two element. They are government and P3A (Perkumpulan Petani Pemakai Air ) Dharma Tirta. Government has responsibility to manage the primary and secondery Irrigation net, and P3A has responsibility to manage the tertiary Irrigation net. To know the ability of P3A to manage the teriary Irrigation net, government has a method, it has standart grade for P3A in Central Java. Every years, the government of Central Java evaluate the progress of each grade of P3A. with the grade, Government classify P3A into 3 group, they are undeveloped, now being developed, andÂ Â developing P3A. Most of P3A in Central Java in the end of 2000 are developing, the second big number are now being developed and the third one are undeveloped.Keywords: P3A, Ability, ClassifyPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/2178[How to cite: Supadi (2008), Kajian Perkumpulan Petani Pemakai Air (P3A) Pasca Reformasi di Provinsi Jawa Tengah, Jurnal Media Komunikasi Teknik Sipil, Tahun 16, No. 1, pp. 99-104]